Sound absorption of microperforated panel made from polylactic acid (PLA) - Chin, Desmond Daniel Vui Sheng; Yahya, Musli Nizam; Che Din, Nazli; Nur Aisyah, Mohamad Nazam; Keng, Yinn Wong; Asyraf, M. R. M.; Sekar, Vignesh (2023)
The microperforated panel (MPP) is a unique panel that has evolved from the traditional perforated panel. Previously, the perforated panel was mainly used as a protective cover for porous materials. The MPP absorbs sound through the viscous effect around its perforated holes. However, traditional MPPs are typically made from metallic materials that are not environmentally friendly. In contrast, polylactic acid (PLA) is a biopolymer extracted from natural resources such as corn and sugarcane. When buried in soil, PLA degrades naturally with the assistance of soil bacteria and fungi, making it an eco-friendly choice. In this study, 3D printing method was utilized to produce MPP using PLA as the material. The sound absorption performance of PLA MPP was compared to steel MPP, which served as the benchmark. Interestingly, the sound absorption performance of PLA MPP was found to be comparable to that of steel MPP. This highlights PLA as a viable material for MPP production, aligning with the global goal of environmental preservation and Sustainable Development Goal (SDG) 12, which emphasizes responsible consumption and production